Acoustical Parameters and Apparent Molar Volume of Lithium Soaps in Methanol - P. Varma, Raghunath; Goel, H. (Asian Journal of Chemistry, 2010)
Ultrasonic velocity and density measurements of lithium soaps (abietate, oleate and myristate) were measured in methanol at different frequencies (1-5 MHz) and under different conditions to determine critical micelle concentration and various acoustical parameters for the soap solutions. The evaluated parameters of ultrasonic velocity and the density data suggest a significant solutesolvent interaction in dilute solution and micellar aggregation at higher concentration.